Petrogenetic interpretation of granitoid rocks using multicationic parameters in the Sanggau Area, Kalimantan Island, Indonesia - Kyaw Linn Zaw; Lucas Donny Setijadji; I Wayan Warmada; Koichiro Watanabe (Journal of Applied Geology, 2015)
Granitoid rock compositions from a range of tectonic environments are plotted on a multicationic diagram, based on major and trace element geochemistry and K-Ar dating. This shows that there is a different tectonic nature, rock affinity and suites. The basement granitoid rocks are ranging from diorite to granite composition. They appear to the products of crystallization differentiation of a calc-alkaline magma of island affinity and range to metaluminous granites, granodiorite and tonalite. The tectonic setting has two kinds which are subduction and post-subduction. The geochemical interpretation, origin and melting of mechanism and tectonic setting shows the types of granitoid are M and I-M type. The basement of granite and granodiorite are a segment of island arc that were happened the Sintang Intrusion as post subduction or syn-collision tectonic setting. Keywords: Petrogenetic, tectonic, affinity, Sintang Intrusion, Kalimantan